Treatment of middle aortic syndrome with thoraco-abdominal aortic bypass grafting assisted by endoscope in adult. (January 2022) - Li, Chuntian; Mao, Xin; Zhao, Xu; Liu, Guiqing; Xu, Gang; Liu, Yang; Yang, Yanmiao; Wang, Hui; Wang, Feng
Middle aortic syndrome (MAS) is a rare disease characterized by distal thoracic aorta or abdominal aorta coarctation, and thoraco-abdominal aortic bypass grafting is an effective treatment for this condition. However, significant trauma is associated with the conventional surgical approach. We report a 26-year-old woman with MAS who presented with hypertension and needed thoraco-abdominal bypass grafting. In this operation, we adopted the endoscopic technique to improve the conventional surgical approach (reduce the incision). This case report shows that it is safe and feasible to use an endoscopic technique to reduce the trauma during this kind of operation, and provides a reference for similar treatments.